Preparing individuals with extremity loss due to earthquake through early rehabilitation program for the future - Altıntaş, Sibel; Çelik, Sevim; Karahan, Elif; Uçar, Özge; Altıntaş, Sibel; Çelik, Sevim; Uçar, Özge; Karahan, Elif (Springer Heidelberg, 2024)
Purpose To mitigate future health risks and improve body image coping strategies among individuals who experienced amputation due to the 2023 Kahramanmara & scedil; earthquake, through an early rehabilitation program. Methods A semi-experimental prospective study was conducted with 18 individuals who experienced amputation due to the earthquake. Data were collected using the Individual Identification Form Amputee Body Image Scale and Body Image Coping Strategies Scale. The earthquake survivors included in the study were provided with a 5-day online interactive rehabilitation training program developed based on expert opinions. Prior to the training, participants were sent healthcare materials to be used during the sessions, interactive practices were conducted throughout the training to enhance individual self-care through interaction with peers and the trainer. Results The average age of individuals who experienced amputation earthquake survivors was 38.72 +/- 14.53 years, with 72.2% being male and 55.6% being married. Among them, 44.4% had leg amputations, and one survivor had lost three extremities. The average scores on the Body Image Coping Strategies Scale showed a statistically significantly increase after the training and at one month post-training compared to before the training (p < 0.05). Conversely, the average scores on the Amputee Body Image Scale showed a statistically significant decrease after the training at one month post-training compared to before the training (p < 0.05). Conclusion The development of early rehabilitation models is essential for improving psychological well-being among individuals who experience amputation following an earthquake.
Keywords: Amputation; Early Rehabilitation; Earthquake; Extremity Loss; Rehabilitation